THE HAZARDOUS SUBSTANCES IN SPECIAL SURFACE TREATMENT OF WOOD PRODUCTS - DANIHELOVA, Anna (Trends in education, 2012)
The surface treatment is an important element in the production of special wood products - musical instruments. It has a protective function, cannot have a negative impact on the nature of the sound of the instrument must also satisfy the aesthetic equirements. In the proces of surface treatment of special wood products are used by a variety of coating substances. Dominated by natural resins, but in some cases are even chemical hazardous substances.
Keywords: surface treatment; hazardous substances; musical instruments; wood.